1980
DOI: 10.2466/pms.1980.50.2.535
|View full text |Cite
|
Sign up to set email alerts
|

Time Estimation Among Schizophrenics

Abstract: Studies of time estimation among schizophrenics have sometimes been difficult to integrate with one another because of differing methodologies and inconsistent definitions. The present study should increase clarity by employing several methods of time estimation within the same study and maintaining a consistent definition of overestimation and underestimation across tasks. 26 schizophrenic and 26 control subjects were given three types of time-estimation tasks. Longer interval Estimation involved judging, at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0
1

Year Published

1984
1984
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 3 publications
4
28
0
1
Order By: Relevance
“…Specifically, individuals diagnosed with schizophrenia have consistently been found to experience time as lengthened relative to objective time, which has been interpreted to reflect an increase in the speed of a hypothetical "internal clock" (Densen, 1977;Johnson & Petzel, 1971;Lhamon & Goldstone, 1956;Tracy et al, 1998;Tysk, 1983aTysk, , 1983bTysk, , 1990Wahl & Sieg, 1990). For instance, numerous behavioral studies have reported overestimations and underproductions of temporal durations ranging from several seconds to one minute in schizophrenia (Densen, 1977;Johnson & Petzel, 1971;Tysk, 1983aTysk, , 1983bTysk, , 1990Volz et al, 2001;Wahl & Sieg, 1980), which is consistent with patients' subjective reports of an elongated experience of time (Freedman, 1974).…”
supporting
confidence: 53%
See 1 more Smart Citation
“…Specifically, individuals diagnosed with schizophrenia have consistently been found to experience time as lengthened relative to objective time, which has been interpreted to reflect an increase in the speed of a hypothetical "internal clock" (Densen, 1977;Johnson & Petzel, 1971;Lhamon & Goldstone, 1956;Tracy et al, 1998;Tysk, 1983aTysk, , 1983bTysk, , 1990Wahl & Sieg, 1990). For instance, numerous behavioral studies have reported overestimations and underproductions of temporal durations ranging from several seconds to one minute in schizophrenia (Densen, 1977;Johnson & Petzel, 1971;Tysk, 1983aTysk, , 1983bTysk, , 1990Volz et al, 2001;Wahl & Sieg, 1980), which is consistent with patients' subjective reports of an elongated experience of time (Freedman, 1974).…”
supporting
confidence: 53%
“…Following this line of thinking, and given that schizophrenia is characterized by profound disturbances in perception, attention, and cognition, it is not surprising that schizophrenia has also been associated with systematic distortions of time (Densen, 1977;Johnson & Petzel, 1971;Tysk, 1983aTysk, , 1983bTysk, , 1990Volz et al, 2001;Wahl & Sieg, 1980). Specifically, individuals diagnosed with schizophrenia have consistently been found to experience time as lengthened relative to objective time, which has been interpreted to reflect an increase in the speed of a hypothetical "internal clock" (Densen, 1977;Johnson & Petzel, 1971;Lhamon & Goldstone, 1956;Tracy et al, 1998;Tysk, 1983aTysk, , 1983bTysk, , 1990Wahl & Sieg, 1990).…”
mentioning
confidence: 99%
“…The most significant results seem to be as follows: schizophrenics overstimate brief durations, whether in estimation at various moments of an interview-testing session or in operational estimation. In this method the S was required to indicate when a specified number of seconds had passed (Wahl & Sieg 1980). This overestimation of brief durations must have been brought out by the well-known characteristic of chronic schizophrenics.…”
Section: Individual Differencesmentioning
confidence: 99%
“…Indeed, research on time estimation in schizophrenia has a long history (Clausen, 1950;Lhamon & Goldstone, 1956;Webster et al 1962;Lhamon et al 1965 ;Orme, 1966;Carlson & Feinberg, 1968), and there have been numerous reports of impaired temporal comprehension in these patients (Dilling & Rabin, 1967;Johnson & Peztel, 1971 ;Lhamon & Goldstone, 1973;Densen, 1977 ;Wahl & Sieg, 1980 ;Tysk, 1983aTysk, , b, 1984Tysk, , 1990Rammsayer, 1990;Tracy et al 1998; though see Webster et al 1962 ;Goldstone et al 1979 ;Crain et al 1975). Studies have indicated that schizophrenic patients are not simply less accurate in time estimation tasks, but show a particular kind of distortion in timing, in that they tend to overestimate time intervals (Tracy et al 1998 ;Tysk, 1983aTysk, , b, 1984Tysk, , 1990.…”
Section: Introductionmentioning
confidence: 99%